British Society for Sexual Medicine Guidelines on the Management of Erectile Dysfunction in Men—2017. Issue 4 (14th March 2018) - Hackett, Geoff; Kirby, Mike; Wylie, Kevan; Heald, Adrian; Ossei-Gerning, Nick; Edwards, David; Muneer, Asif
Abstract: Background: This is an update of the 2008 British Society for Sexual Medicine (BSSM) guidelines. Aim: To provide up-to-date guidance for U.K. (and international) health care professionals managing male sexual dysfunction. Methods: Source information was obtained from peer-reviewed articles, meetings, and presentations. A search of Embase, MEDLINE, and Cochrane Reviews was performed, covering the search terms "hypogonadism, " "eugonadal or hypogonadism or hypogonadal or gonadal, " and "low or lower testosterone, " starting from 2009 with a cut-off date of September 2017. Outcomes: We offer evidence-based statements and recommendations for clinicians. Results: Expert guidance for health care professionals managing male sexual dysfunction is included. Clinical Translation: Current U.K. management has been largely influenced by non-evidence guidance from National Health Service departments, largely based on providing access to care limited by resources. The 2008 BSSM guidelines to date have been widely quoted in U.K. policy decision making. Conclusions: There is now overwhelming evidence that erectile dysfunction is strongly associated with cardiovascular disease, such that newly presenting patients should be thoroughly evaluated for cardiovascular and endocrine risk factors, which should be managed accordingly. Measurement of fasting serum glucose, lipid profile, and morning total testosterone should be considered mandatory in all newly presenting patients. Patients attending their primary care physician with chronic cardiovascular disease should be asked about erectile problems. There can no longer be an excuse for avoiding discussions about sexual activity due to embarrassment.